Water balance of the basin of Mandali/ east part of Iraq - AL-Kubaisi, Qusai Y. (Iraqi Journal of Physics, 2019)
Mandali Basin is located between latitudes (33◦ 39’ 00" and 33◦ 54’ 55") to the north and longitudes (45ο 11’ 00" and 45ο 40’ 00") to the east; to the east of Diyala province at the Iraqi-Iranian border; the basin area is approximately 491 km2. From the study of climate reality of the basin between 1990- 2013and assessment of the basic climate transactions, it was found that the annual rate of rainfall is 253.02 mm, the relative humidity (44.4%), the temperature (21.3 ◦C), wind speed (2.08 m /sec.), sunshine (8.27 h/day) and evaporation of the basin class (a) (271.98 mm) and corrected potential evapotranspiration (80.03 mm). The results of the data analysis show that, there are three basic periods of climate variability wet period, semi wet and dry period. This study shows that, there is water surplus of 60.87% of the rainfall amount which is equivalent to 154.03 mm, the amount of runoff is 7.47 mm, and the amount of water recharge is 146.56mm.